Mighty bugs: leprosy bacteria turn schwann cells into stem cells. - Wegner, Michael (Cell, 2013)
For intracellular parasites that strongly prefer infecting a particular cell type, systemic spread is challenging. Masaki et al. show that the leprosy bacterium cleverly expands its repertoire by driving dedifferentiation of Schwann cells, their preferred host, to cells with stem cell properties that can subsequently redifferentiate into mesodermal lineages. © 2013 Elsevier Inc.
UnivIS-Import:2015-03-09:Pub.2013.med.IB.LPCIPDBI.mighty